A novel mayonnaise-type dressing added with avocado pulp and oil as health ingredients processed with ultrasound. Issue 1 (31st December 2022) - Guzmán-Gerónimo, Rosa Isela; Ayala-Tirado, Rosa Carmina; Mendoza-López, Remedios; Cocotle-Ronzón, Yolanda; Herrera-Meza, María Del Socorro
ABSTRACT: In this study, avocado pulp and oil were added to mayonnaise type-dressing to produce a healthy and microbiologically safe product with improved sensory properties. First, oil avocado was obtained by solvent-free ultrasonic-assisted extraction and centrifugation. The mayonnaise type-dressing was formulated with avocado pulp and oil and then treated with ultrasound. Chemical and sensory qualities were determined in the oil. Microbiological quality, color and sensory analysis were carried out in the mayonnaise type-dressing along a storage period under refrigeration. The avocado oil yield was 64% with an outstanding emerald green color. The avocado oil quality agreed with Mexican Official Standards. Oleic, palmitic, palmitoleic and linoleic acids were found to be the major fatty acids in avocado oil. The mayonnaise-type dressing showed a reduction of the microbial load without the need for thermal pasteurization, and the green color was stable during storage. Color, odor and flavor were sensorially evaluated as "like much."